Association of fear of falling and low physical activity with fall risk among older Taiwanese community-dwellers - Yih-Jian Tsai; Wen-Jung Sun; Yi-Ching Yang; Mei-Yu Wei (BMC, 2024)
Abstract Background and purpose Fear of falling and low physical activity become prevalent in an aged society, but their association with fall risk warrants further investigation. Methods Our study involved 600 individuals aged 70.8-96.1 years who completed two rounds of community surveys. During the second survey, we analyzed the correlations between fall incidents and a range of factors, including age, sex, gait maneuverability, vision, comorbidity count, depressive symptoms, cognitive function, history of falls, fear of falling, and physical activity level. The chi-square test and univariate and multivariate logistic regression models were used, with further analyses either adjusted for or stratified by the full-factor combinations of fear of falling (with versus without) and low physical activity (low versus moderate-to-high). Results Falls exhibited a prevalence rate of 13.8%. A fall risk gradient by the full-factor combinations was observed. Multivariate logistic regression modeling identified independent risk predictors for falls, including the number of comorbidities, depressive symptoms, a history of falls, and fear of falling. Fear of falling and low physical activity presented a synergistic effect to increase the fall risk by two- and one-third times (adjusted odds ratio: 2.35, 95% confidence interval: 1.12-4.91). Depressive symptoms, cognitive impairment, and a history of falls remained as significant risk predictors for older adults with both factors, those with fear of falling only, and those with neither, respectively, when the models were further stratified. Conclusion Fear of falling and low physical activity presented likely synergism to increase the fall risk. Those older community-dwellers with both risk factors warrant fall prevention resources as a priority over those with either or neither.